La mediación social a través del uso de mitologemas sobre la Amazonía en la prensa brasileña - Stefanello , Grace (Mediaciones Sociales, 2008)
The present article refers to a doctoral research concluded in 2007. Brazilian press stories were analyzed, having as a point of reference the Amazonia in two moments of Brazilian history: dictatorship and democracy. The thesis included the mediation analysis to relate the myths and the written production on Amazonia. For this purpose we used the contributions of the Theory of Social Communication, the Mediation Paradigm, with the help of the structuralist methodology and tools of logical and statistical analysis.
Keywords: Mediation; Content analysis; Mythologem; Amazonia; History